NAVIGATING HEMINGWAY’S DEPTHS: AN ICEBERG ANALYSIS OF THEMES AND SYMBOLISM IN THE OLD MAN AND THE SEA - Muhammad Iqbal; Fareeha Zaheer; Tanveer Baig (International Journal of Contemporary Issues in Social Sciences, 2024)
This paper delves into the depths of Hemingway’s The Old Man and the Sea utilizing Iceberg theory. By exploring the surface narrative of an old fisherman’s relentless struggle with a giant marlin, we uncover the submerged themes and symbols that form the bedrock of the story. Central to our analysis is the examination of resilience, dignity, and the human condition, as exemplified by the protagonist, Santiago. The paper investigates how Hemingway’s laconic style conceals a wealth of deeper meanings related to nature and the eternal struggle between man and his environment. Through a close reading of key passages and symbols, such as the marlin, the sea, and the lions on the beach, the paper reveals the intricate layers of significance embedded in the text. The current study aims to highlight Hemingway’s mastery in crafting a narrative that, much like an iceberg, extends far beyond what is immediately visible, inviting readers to ponder the profound truths lying beneath the surface.